The Role of Family in Pain Management among Patients with Chronic Illness - Amita Audilla; Farida; Nurhidayati; Surtini; Suharyoto (Al-Hijrah Indonesia, 2026)
Chronic diseases are major health problems often accompanied by persistent pain that can reduce patients’ quality of life. Pain management is not only dependent on medical therapy but is also influenced by the role of the family as the primary support system. The purpose of this study was to determine the relationship between family role and pain management among patients with chronic illness. This study used a quantitative, cross-sectional design. The sample consisted of 35 respondents selected using total sampling in Boyolangu Village, Tulungagung Regency. Data were collected using a family role questionnaire, and pain level was measured using the Numeric Rating Scale (NRS). The study was conducted in January 2026. Data analysis was performed using univariate and bivariate analysis with the Spearman Rank test. The results showed that most respondents had a good family role (57.1%). The majority of respondents (48.6%) experienced moderate pain. Bivariate analysis indicated a significant relationship between family role and pain level (p = 0.002; p < 0.05). The correlation coefficient (r = -0.45) showed a moderate negative relationship, meaning that better family role was associated with lower pain levels. In conclusion, there is a significant relationship between family role and pain management among patients with chronic illness; therefore, healthcare providers are encouraged to enhance family involvement in pain management to improve patients’ quality of life.